2021
DOI: 10.19206/ce-143245
|View full text |Cite
|
Sign up to set email alerts
|

Ecological aspects of using mixtures of canola oil with n-hexane in diesel engine

Abstract: The article discusses the results of research on the use of canola oil and canola oil with the addition of n-hexane in a compression-ignition engine. An engine with a Common Rail injection system was tested in real traffic conditions on the road and on a chassis dynamometer. The tested fuels were fed to the engine by an additional fuel supply system. An analysis of the effect of the addition of n-hexane on the emission of the main components of toxic exhaust gases was carried out. The proposed solution may con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The use of unprocessed jatropha oil as fuel may be difficult due to its high density and density. However, other than blending with kerosene, the high viscosity could also be significantly reduced with the addition of n-hexane, save that it could generate a negating ecological condition due to the increased concentration of nitrogen oxides, as it is with canola oil [23]. Existing literature has also revealed that that fish waste and jatropha oil can be used as alternate fuel for engines without modifying any specifications of the engine, and also, the emissions from the engine showed a better result except NO x which is higher [24].…”
Section: Introductionmentioning
confidence: 99%
“…The use of unprocessed jatropha oil as fuel may be difficult due to its high density and density. However, other than blending with kerosene, the high viscosity could also be significantly reduced with the addition of n-hexane, save that it could generate a negating ecological condition due to the increased concentration of nitrogen oxides, as it is with canola oil [23]. Existing literature has also revealed that that fish waste and jatropha oil can be used as alternate fuel for engines without modifying any specifications of the engine, and also, the emissions from the engine showed a better result except NO x which is higher [24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, modern fuel injection systems (Common Rail) are used, which operate on the basis of appropriate precisely-selected control strategies stored in the ECU (Engine Control Unit). The use of alternative fuels in diesel engines, based on vegetable oils (rapeseed oil, soybean oil and others), due to significant differences in physicochemical properties (in particular, viscosity) relative to ON, is difficult [32][33][34][35][36][37][38][39][40][41][42][43]. Therefore, to counteract these problems, attempts have been made to modify the engine itself (Ellsbett technology) as well as its accessories (fuel heating systems, dual-fuel systems) [44].…”
Section: Introductionmentioning
confidence: 99%